2023
DOI: 10.1371/journal.pone.0271081
|View full text |Cite
|
Sign up to set email alerts
|

MYB and ELF3 differentially modulate labor-inducing gene expression in myometrial cells

Abstract: Spontaneous uterine contractions are initiated when smooth muscle cells (SMCs) within the uterine muscle, or myometrium, transition from a functionally dormant to an actively contractile phenotype at the end of the pregnancy period. We know that this process is accompanied by gestational time point-specific differences in the SMC transcriptome, which can be modulated by the activator protein 1 (AP-1), nuclear factor kappa beta (NF-κβ), estrogen receptor (ER), and progesterone receptor (PR) transcription factor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…We assessed whether the transactivation potential of the AP-1 dimer combinations on the Gja1 and Fos gene promoters is altered in the presence of SOX4 (Fig 4A/B). Note that the two controls ( Gja1 and Fos promoter activities indicated by asterisks in Fig 4A/B) increased with the addition of JUND, and were significantly elevated in the presence of JUND and FOSL2 proteins, as previously reported (8). Here we show that the addition of SOX4 does not significantly activate the Gja1 promoter, either on its own or in association with the AP-1 proteins, despite the presence of a strong SOX4 motif in the promoter sequence (Fig 4A).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…We assessed whether the transactivation potential of the AP-1 dimer combinations on the Gja1 and Fos gene promoters is altered in the presence of SOX4 (Fig 4A/B). Note that the two controls ( Gja1 and Fos promoter activities indicated by asterisks in Fig 4A/B) increased with the addition of JUND, and were significantly elevated in the presence of JUND and FOSL2 proteins, as previously reported (8). Here we show that the addition of SOX4 does not significantly activate the Gja1 promoter, either on its own or in association with the AP-1 proteins, despite the presence of a strong SOX4 motif in the promoter sequence (Fig 4A).…”
Section: Resultssupporting
confidence: 85%
“…Significantly different results (p<0.05) are indicated by groups labeled with different letters. Asterisk (*) in (A) and (B) indicates control groups as previously reported in (8).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Having established that murine myometrium display increased levels of SOX4 protein at the onset of both term and preterm labor, we next sought to ascertain whether SOX4 exerts a functional role in the transcriptional control of labor-associated genes which contain strong binding motifs for both AP-1 and SOX4. We used a luciferase reporter assay as a means of measuring promoter regulation in transfected Syrian hamster myometrium (SHM) cells [ 8 , 13 , 17 ]. We used previously generated luciferase constructs with the reporter gene under the control of the well-studied labor-associated promoters from the Gja1 and Fos genes [ 8 ] to assess the regulatory capacity of SOX4, either on its own or alongside AP-1 factors.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we found that two additional factors, MYB and ELF3, exhibit differential expression in pre-laboring and laboring human and murine myometrium as SMCs undergo the quiescent-to-contractile transition. We found that despite being upregulated at labor onset, these factors play opposing roles in stimulating expression from labor-associated gene promoters, with MYB having an activating and ELF3 a repressive role [ 8 ].…”
Section: Introductionmentioning
confidence: 99%